TATA KERJA BAZNAS MEMOTIVASI PEKEBUN JERUK UNTUK MEMBAYAR ZAKAT di KECAMATAN TALAMAU KABUPATEN PASAMAN BARAT - Nora Zulvianti; Susi Yermalina (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2022)
The purpose of this study is to find out and reveal how BAZNAS motivates the community to increase paying zakat through motivation, good communication and instilling cooperation carried out by the BAZNAS institution in West Pasaman Regency. The research method used is a qualitative method with a descriptive approach. From this study, it is known that BAZNAS motivates citrus planters to increase paying zakat in Talamau District, West Pasaman Regency with the following explanation: (1) BAZNAS's motivation is in the form of socialization and direct visits to the community. Provide encouragement and invitations to citrus planters to pay their zakat to BAZNAS, and provide direction on the importance of tithing. (2) The application of communication carried out by BAZNAS is in the form of oral and written communication. Examples of oral communication carried out include conveying about the BAZNAS program and to whom the zakat they pay is distributed. While in written form, namely in the form of a letter signed directly by the leader who is given directly to the person concerned or the orange planter. (3) The implementation of the cooperation carried out by BAZNAS is to submit a letter signed by the leader which is given to jorong or community leaders which will later be submitted to citrus planters, and to collaborate with mosque administrators to give 30% of the zakat proceeds given by the mosque's muzakki given to BAZNAS to be managed and distributed.